Internalizing Humanism in Islamic Religious Education: The Role of Teachers as Facilitators of Psychological Safety in Students’ Self-Actualization - Maslani Maslani; Ainul Mardhiyyah; Dicky Alfian Nur Rachman; Rika Haulina; Syahru Ramadhan (Vifada Journal of Education, 2026)
This study explores the role of Islamic Religious Education teachers as facilitators of psychological safety in internalizing humanistic values and supporting students’ self-actualization. Contemporary challenges in Islamic education are no longer limited to the transmission of religious knowledge; they also encompass identity crises, moral degradation, and the increasing vulnerability of mental health among Generation Z students. Employing a qualitative library research method with critical discourse and intertextual analysis, this article integrates the concept of psychological safety in modern educational psychology with Islamic humanism rooted in the concepts of *fitrah* and human beings as *khalifah*. The findings indicate that Islamic Religious Education teachers play a strategic role in creating psychologically safe classrooms through dialogical, inclusive, and humanistic approaches, including the implementation of Problem-Based Learning and case study methods. Such a learning environment enables students to think critically, express their ideas openly, and develop their innate potential optimally. This study concludes that the success of Islamic education should not be measured solely by cognitive achievement, but also by students’ holistic development, encompassing intellectual, spiritual, moral, and social dimensions. Conceptually, this study contributes by offering a synthesis between modern educational psychology and Islamic humanism, while also providing practical implications for Islamic Religious Education teachers in responding to the complexities of contemporary education